2021
DOI: 10.3389/fphys.2021.645646
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transport and Metabolism at the Blood-Brain Interface: Implications in Health and Disease

Abstract: Many prospective studies have shown that a diet enriched in omega-3 polyunsaturated fatty acids (n-3 PUFAs) can improve cognitive function during normal aging and prevent the development of neurocognitive diseases. However, researchers have not elucidated how n-3 PUFAs are transferred from the blood to the brain or how they relate to cognitive scores. Transport into and out of the central nervous system depends on two main sets of barriers: the blood-brain barrier (BBB) between peripheral blood and brain tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 87 publications
0
44
0
Order By: Relevance
“…In order to cross the BBB, there are essentially three potential pathways: passive diffusion through the endothelial membrane, active transport via transfer into the en-dothelium by transmembrane protein transporters (transcytosis), or receptor-mediated endocytosis [68].…”
Section: Discussionmentioning
confidence: 99%
“…In order to cross the BBB, there are essentially three potential pathways: passive diffusion through the endothelial membrane, active transport via transfer into the en-dothelium by transmembrane protein transporters (transcytosis), or receptor-mediated endocytosis [68].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is widely recognized that cholesterol is unable to pass through the blood-brain barrier owing to the presence of tight junctions [167], interestingly, one study has reported direct transport of free cholesterol across the blood-brain barrier via ABCA1 in mice [168]. It also remains possible that physiological and morphological changes to the blood-brain barrier as a result of age or neurodegenerative disease may compromise its permeability, rendering a greater likelihood of leakage of substances, including cholesterol, into and out of the brain [169]. Indeed, increased leakage of oxysterols out of the brain at the blood-brain barrier has been reported in pericyte-deficient mice [170].…”
Section: Direct Export From Brainmentioning
confidence: 99%
“…Interestingly, microglia appear to be highly susceptible to modulation by dietary lipids and other nutrients that are taken up by the brain ( Butler et al., 2020 ; Nadjar et al., 2017 ; Sobesky et al., 2014 ; Spencer et al, 2017 , 2019 ). Preclinical models have shown that SFAs consumed via HFDs can cross the BBB via transport-protein mediated mechanisms ( Pifferi et al., 2021 ). Once in the brain, SFAs can activate toll-like receptors (TLRs), which are located on the surface membrane of innate immune cells like microglia ( Nadjar et al., 2017 ).…”
Section: Brain-resident and Infiltrating Immune Cellsmentioning
confidence: 99%